2017
DOI: 10.1371/journal.pone.0182931
|View full text |Cite
|
Sign up to set email alerts
|

Contests over reproductive resources in female roller beetles: Outcome predictors and sharing as an option

Abstract: Fights among females are frequent, although less attention has been placed on them than on male fights. They arise when females compete for food, oviposition, mates, brooding sites, or access to resources which increase offspring survival. It has been shown that the outcome of female fights may be less predictable by asymmetries in resource holding power, than in male fights. Male roller beetles fight over food resources, food balls, needed for mating and nesting, and it has been show in some species that asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Males of C. cyanellus with higher body dry mass and larger body size were more successful in contests for food. Our results corroborate previous studies performed with C. cyanellus reared under laboratory conditions, which showed that larger males have higher probabilities to win contests for females (Chamorro‐Florescano et al, , ). In addition, heavier males showed a significantly shorter latency to start ball‐rolling with females.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Males of C. cyanellus with higher body dry mass and larger body size were more successful in contests for food. Our results corroborate previous studies performed with C. cyanellus reared under laboratory conditions, which showed that larger males have higher probabilities to win contests for females (Chamorro‐Florescano et al, , ). In addition, heavier males showed a significantly shorter latency to start ball‐rolling with females.…”
Section: Discussionsupporting
confidence: 93%
“…As this study was conducted in the field, a larger sample size could not be obtained; therefore, it is important to interpret the results with caution, as some significant effects may not be detected with low sample sizes due to low statistical power. However, the number of samples was similar to other studies behavioral studies conducted with C. cyanellus in controlled conditions, which presented strong, statistically significant effects (Chamorro‐Florescano & Favila, ; Chamorro‐Florescano et al, , ). This confirms that the behavioral responses measured in our study are strong enough to be detected despite the low statistical power resulting from the low sample size.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…RHP is commonly determined by the size of an individual and its weapons or factors linked to its condition, such as persistence capacity or strength (for review see Vieira and Peixoto, 2013). For example, larger competitors can be more likely to win an interaction against smaller or less experienced individuals (Chamorro-Florescano et al, 2011). However, RV can influence contest occurrence and outcome (Stockermans and Hardy, 2013); for example, females with offspring are more likely to win contests against males over burrows than females without offspring (Figler et al, 1995).…”
Section: Introductionmentioning
confidence: 99%